Comparing the Efficacy of Angiotensin Converting Enzyme Inhibitors with Calcium Channel Blockers on the Treatment of Diabetic Nephropathy: A Meta-Analysis - Zhaowei ZHANG; Chunlin CHEN; Shiwen LV; Yalan ZHU; Tianzi FANG (Tehran University of Medical Sciences, 2019)
Background: The angiotensin-converting enzyme inhibitors (ACEIs) could improve the symptoms of diabetic nephropathy. Whether the calcium channel blockers (CCBs) could be as effective as ACEIs on treating diabetic nephropathy is controversial. Here, we aimed to compare the efficacy of ACEIs with CCBs on the treatment of diabetic nephropathy by performing a meta-analysis of randomized controlled trials (RCTs). Methods: The Pubmed, Medline, Embase and The Cochrane Database were searched up to July 2017 for eligible randomized clinical trials studies. Effect sizes were summarized as mean difference (MD) or standardized mean difference (SMD) with 95% confidence intervals (P-value<0.05). Results: Seven RCTs involving 430 participants comparing ACEIs with CCBs were included. No benefit was seen in comparative group of ACEIs on systolic blood pressure（SBP） (MD=1.05 mmHg; 95% CI: -0.97 to 3.08, P=0.31), diastolic blood pressure (DBP) (MD= -0.34 mmHg; 95% CI: -1.2 to 0.51, P=0.43), urinary albumin excretion rates (UAER) (MD=1.91μg/min; 95% CI: -10.3 to 14.12, P=0.76), 24-h urine protein (24-UP) (SMD=-0.26; 95%CI: -0.55 to 0.03, P=0.08), glomerular filtration rate (GFR) (SMD=0.01; 95% CI: -0.38 to 0.41, P=0.95). On safety aspect, the risk of adverse reactions between ACEIs group and CCBs group are similar (RR=1.18; 95% CI: 0.61 to 2.28; P=0.61). Conclusion: Both ACEIs and CCBs could improve the BP, UAER, 24h-UP, and GFR of diabetic nephropathy to a similar extent.